The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1516-89132011000300020
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of drying and adsorption isotherms of the fish feed

Abstract: The aim of this work was to study the drying curves and equilibrium isotherms of extruded fish feed. The drying curves were determined at air temperatures of 50, 60, 70 and 80°C and airflow velocities of 1.5, 2.5 and 3.5 m/s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…Sousa et al (2006) também verificaram elevação no parâmetro "n" para o modelo de Page, ao desidratar farelo de mamona. Pacheco et al (2011) secaram cogumelos nas temperaturas de 50, 60, 70 e 80 °C e velocidades do ar de 1,5, 2,5 e 3,5 m s -1 e constataram que, para a velocidade do ar de 1,5 m s -1 , o modelo de Page também teve o parâmetro "n" aumentado com a elevação da temperatura de secagem. Jittanit (2011) ajustou o modelo de Page aos dados experimentais da secagem de sementes de abóbora em secador de bandejas nas temperaturas de 60, 70 e 80 °C e observou comportamento contrário, visto que o parâmetro "n" diminuiu com a elevação da temperatura de secagem.…”
Section: Rx X X X Xunclassified
“…Sousa et al (2006) também verificaram elevação no parâmetro "n" para o modelo de Page, ao desidratar farelo de mamona. Pacheco et al (2011) secaram cogumelos nas temperaturas de 50, 60, 70 e 80 °C e velocidades do ar de 1,5, 2,5 e 3,5 m s -1 e constataram que, para a velocidade do ar de 1,5 m s -1 , o modelo de Page também teve o parâmetro "n" aumentado com a elevação da temperatura de secagem. Jittanit (2011) ajustou o modelo de Page aos dados experimentais da secagem de sementes de abóbora em secador de bandejas nas temperaturas de 60, 70 e 80 °C e observou comportamento contrário, visto que o parâmetro "n" diminuiu com a elevação da temperatura de secagem.…”
Section: Rx X X X Xunclassified
“…The initial moisture of the SCR based fish feed was found out by gravimetric method to be 22% on a wet basis. Ana et al [2] also had a similar result.…”
Section: Moisture Content Of Scr Based Fish Feedmentioning
confidence: 54%
“…[1]. Ana et al [2] reported that one of the major hindrances to the successful practice of fish production is fish feed. Feed formulation involves the combination of feed ingredients to meet the requirements of the intended fishes [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations